A critical review of disproportionality in loss and damage from climate change. (23rd February 2022) - Dorkenoo, Kelly; Scown, Murray; Boyd, Emily
Abstract: The notion of disproportionate impacts of climate change on certain groups and regions has long been a part of policy debates and scientific inquiry, and was instrumental to the emergence of the "Loss and Damage" (L&D) policy agenda in international negotiations on climate change. Yet, 'disproportionality' remains relatively undefined and implicit in science on loss and damage from climate change. A coherent theoretical basis of disproportionality is needed for advancing science and policy on loss and damage. It is necessary to ask: What is disproportionate, to whom, and in relation to what? We critically examine the uses of disproportionality in loss and damage scholarship by analyzing how disproportionality is treated in the literature conceptually, methodologically, and empirically. We review publications against a set of criteria derived from seminal work on disproportionality in other fields, mainly environmental justice and disaster studies that have analyzed environment–society interactions. We find disproportionality to be dynamic and multidimensional, spanning the themes of risks, impacts, and burdens. Our results show that while the concept is often used in loss and damage scholarship, its use relies on unarticulated notions of justice and often lacks conceptual, methodological and empirical grounding. Disproportionality also appears as a boundary concept, enabling critical and multiscalar explorations of historical processes that shape the uneven impacts of climate change, alongside social justice and normative claims for desired futures. This emerging area of science offers an opportunity to critically re‐evaluate the conceptualization of the relationship between climate‐change‐related impacts, development, and inequality. This article is categorized under: Climate, Nature, and Ethics > Climate Change and Global Justice Climate and Development > Social Justice and the Politics of Development Abstract : Uses of disproportionality in scholarship on loss and damage from climate change and implications for policy and practice.